2015
DOI: 10.1016/j.bpj.2015.10.041
|View full text |Cite
|
Sign up to set email alerts
|

In-Cell Solid-State NMR: An Emerging Technique for the Study of Biological Membranes

Abstract: Biological molecular processes are often studied in model systems, which simplifies their inherent complexity but may cause investigators to lose sight of the effects of the molecular environment. Information obtained in this way must therefore be validated by experiments in the cell. NMR has been used to study biological cells since the early days of its development. The first NMR structural studies of a protein inside a cell (by solution-state NMR) and of a membrane protein (by solid-state NMR) were publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…In-cell solid-state NMR is an emerging field that requires new tools to expand its range of applicability, and 31 P NMR is underrepresented as one of these tools (44,45). Recently, 2 H NMR has been adapted to in-cell and even in vivo solid-state NMR to characterize lipid acyl chains in intact bacterial membranes and examine the effect of antimicrobial peptides (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…In-cell solid-state NMR is an emerging field that requires new tools to expand its range of applicability, and 31 P NMR is underrepresented as one of these tools (44,45). Recently, 2 H NMR has been adapted to in-cell and even in vivo solid-state NMR to characterize lipid acyl chains in intact bacterial membranes and examine the effect of antimicrobial peptides (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Specific interactions, even transient interactions, with other cellular components will slow tumbling, resulting in broad resonances that are beyond detection. Solid-state NMR is not limited by molecular tumbling rate and therefore may be a better option for studying large-cell surface PSs (91,92). By using the high-resolution magic-angle spinning (HR-MAS) technique, Jachymek et al (93) demonstrated that the immunodominant O-polysaccharide on bacterial surfaces had the same structure as that in lipopolysaccharides and in isolated PSs.…”
Section: Magnetic Resonance Studies Of Cell Surface Carbohydratesmentioning
confidence: 99%
“…In-cell solution NMR spectroscopy has already been well established [114117], with notable applications including the maturation of human superoxide dismutase [118,119], in cell characterization of alpha synuclein [120], and investigations of the relationship between molecular crowding and protein interactions [121,122]. In-cell solid state NMR [123], while a much less mature field, has been demonstrated to have promise on systems such as membrane proteins [124] or proteins in large complexes [125]. Many proteins of interest are dilute in cell, and have concentrations below the limit of detection for traditional solid-state NMR methods.…”
Section: Dnp In Cell Applications: Challenges and Opportunitiesmentioning
confidence: 99%